Designing future dairy systems for New Zealand using reflexive interactive design. (May 2020) - Romera, A.J.; Bos, A.P.; Neal, M.; Eastwood, C.R.; Chapman, D.; McWilliam, W.; Royds, D.; O'Connor, C.; Brookes, R.; Connolly, J.; Hall, P.; Clinton, P.W.
Abstract: Globally, agricultural systems are facing unprecedented challenges. The problems are of systemic nature and will require transformational changes and systemic redesign. In this study, we investigated the redesign of dairy systems in New Zealand, due to their large economic, social and environmental influence nationally. We did not set the boundaries of the 'dairy systems' from the outset, letting this definition be part of the design process. We applied 'Reflexive Interactive Design' (RIO), an approach aimed at structurally addressing complex trade-offs and contributing, by process and design, to change towards sustainable development and integral sustainability (i.e. in all relevant dimensions of sustainability). A detailed system analysis was conducted, followed by two rounds of structured design focused on four main stakeholders ('actors') identified as part of the RIO process: the farmers, the citizens, the consumers, and the dairy cows. Our study established design goals related to enhancing the wellbeing of humans and animals, enhancing environmental performance, economics and resilience of dairy systems and reconnecting dairy farming with the rest of society. The process took us beyond the boundaries of a dairy farm and identified the territorial level as the object of design, arriving at a design concept we have called the ' Agro-ecological Park '. The name was chosen to convey an analogy with 'Eco-industrial Parks'. Operating as a multifunctional network, the Park has the goal of delivering multiple benefits for its members, and multiple goods and services for the rest of society. The coordinated network articulates linkages between farmers and many other businesses and people in the territory. The individual dairy farm is redesigned to be a node in that network rather than operating as an isolated entity. That way, much of the weight for the increased complexity and multifunctionality now demanded of farming can be carried by the network instead of the individual farmer. These preliminary design ideas, and the reasoning behind them, should encourage new perspectives on the complex problems facing NZ dairy farming, and agriculture globally, in the upcoming decades. Highlights: We explored redesigning of dairying in New Zealand towards integral sustainability. We used 'Reflexive Interactive Design' (RIO), a structured design approach. The process led to set the boundaries of our design object at the territory level. We developed a design concept that we have called the ' Agro-ecological Park '. A coordinated network of farmers, many other businesses and actors in the territory.